PTX3 Predicts Myocardial Damage and Fibrosis in Duchenne Muscular Dystrophy - Farini, Andrea; Villa, Chiara; Di Silvestre, Dario; Bella, Pamela; Tripodi, Luana; Rossi, Rossana; Sitzia, Clementina; Gatti, Stefano; Mauri, Pierluigi; Torrente, Yvan (Frontiers in Physiology, 2020)
Pentraxin 3 (PTX3) is a main component of innate immune system by inducing complement pathway activation, acting as inflammatory mediator, coordinating the functions of macrophages/dendritic cells and promoting apoptosis/necrosis. Additionally, it has been found in fibrotic regions co-localizing with collagen. In this work we wanted to investigate the predictive role of PTX3 in myocardial damage and fibrosis of Duchenne Muscular Dystrophy (DMD). DMD is an X-linked recessive disease caused by mutations of dystrophin gene that affects muscular functions and strength and accompanying dilated cardiomyopathy. Here, we expound the correlation of PTX3 cardiac expression with age and TLRs/IL1R-MyD88 inflammatory markers and its modulation by the so-called alarmins IL-33, HMGB1 and S100beta. These findings suggest that cardiac levels of PTX3 might have prognostic value and potential in guiding therapy for DMD cardiomyopathy.